“Why I don’t wish to get married”: desisting marriage at the dissent trials in Nueva Galicia in the late XVIII century. - Cervantes Cortés, José Luis (Universidad Pedagógica y Tecnológica de Colombia, 2016)
In the Hispanic world, the implementation of the “Real pragmática de matrimonios” [Royal sanction for marriage], in 1776, originated a great amount of family controversy, due to the matrimonial choice made by the children of the family. On the one hand, parents defended the lineage and reputation of their families, while the children chose to express their free will to marry. Several lawsuits were iled before the courts in order to solve these conlicts. This is the context in which the present research project is framed, where eight dissent trials were analyzed, that ended with the rejection of the marriage proposal by the female part, without having to justify the reasons concerning to their decision. Nevertheless, in reading these cases, external inluences over the speech of the young ladies are evident, convincing them to avoid the fulillment of the weddings. We can also identify different strategies used by the parents such as the “deposit of wives” in the homes of honorable families or other places suggested by the jury, discrediting the reputation of the iancé or reinforcing patriarchal authority, in order to dissuade them from engaging in these marital unions.